2015
DOI: 10.1063/1.4938398
|View full text |Cite
|
Sign up to set email alerts
|

Phase stability and magnetic behavior of FeCrCoNiGe high-entropy alloy

Abstract: We report an alternative FeCrCoNiGe magnetic material based on FeCrCoNi high-entropy alloy with Curie point far below the room temperature. Investigations are done using first-principles calculations and key experimental measurements. Results show that the equimolar FeCrCoNiGe system is decomposed into a mixture of face-centered cubic and body-centered cubic solid solution phases. The increased stability of the ferromagnetic order in the as-cast FeCrCoNiGe composite, with measured Curie temperature of 640 K, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…These include their use as protective coatings owing to their good corrosion and wear resistance 1,80,84,115,170,171,[219][220][221][222][223][224][225][226][227][228][229][230][231] (see review of laser-deposited HEA coatings by Zhang et al 232 ), as alloys for bulk metallic glasses, 11,[233][234][235][236] and even as materials for hydrogen storage 237 and diffusion barriers. 1,181,182 There has also been interest in their magnetic 1,10,97,[238][239][240][241][242][243] and thermoelectric properties. 244 These properties and applications, and others, are discussed in more detail in the reviews by Zhang et al 14 and Tsai et al 6 The authors consider one of the most promising potential applications for HEAs is as structural materials, and this is addressed specifically in the following text.…”
Section: A Route For Alloy Developmentmentioning
confidence: 99%
“…These include their use as protective coatings owing to their good corrosion and wear resistance 1,80,84,115,170,171,[219][220][221][222][223][224][225][226][227][228][229][230][231] (see review of laser-deposited HEA coatings by Zhang et al 232 ), as alloys for bulk metallic glasses, 11,[233][234][235][236] and even as materials for hydrogen storage 237 and diffusion barriers. 1,181,182 There has also been interest in their magnetic 1,10,97,[238][239][240][241][242][243] and thermoelectric properties. 244 These properties and applications, and others, are discussed in more detail in the reviews by Zhang et al 14 and Tsai et al 6 The authors consider one of the most promising potential applications for HEAs is as structural materials, and this is addressed specifically in the following text.…”
Section: A Route For Alloy Developmentmentioning
confidence: 99%
“…7 It was observed that the T C increased to 355 K and 640 K when Al and Ge, respectively, were added to the FeCoNiCr alloy. 8 The change in T C was accompanied by structural decomposition into a mixture of FCC and BCC solid solution phases. In this work, the effect of non-magnetic components on the ferromagnetic transition and magnetic behaviors of equiatomic FeCoNiCrX (X=Al, Ga, Mn and Sn) HEAs was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The term cocktail effect refers to the fact that some properties (e.g., mechanical or magnetic ones) cannot be approximated from linear interactions among the different elements and phases. This class of alloys has attracted a lot of attention due to promising mechanical [4][5][6][7][8], electric [9,10] and magnetic properties [11,12]. The core effects have originally been assumed to be responsible for the excellent properties of HEAs.…”
Section: Introductionmentioning
confidence: 99%